Strategi Resiliensi Usaha Jasa Co-Working Space Terhadap Krisis Di Kawasan Pariwisata Canggu, Kecamatan Kuta Utara - Gunawan, Michaellino Aprilliando; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 11 No 1 (2023): VOL 11, NO 1 (2023): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i01.p17, 2023)
This research was conducted to analyze the resilience strategy of the co-working space business in the Canggu Tourism Area against a crisis. Meanwhile, to analyze the data in this study used the four-function adaptive cycle concept application. The data used in this study is qualitative data obtained from primary and secondary data sources. Data collection techniques in this study consisted of interviews, observation, literature study, and documentation. The results showed that there were two stages in the four-function adaptive cycle that were not passed by co-working space business in the Canggu Tourism Area during the crisis, namely the growth phase and the conservation phase. Meanwhile, two other stages, namely the release phase and the reorganization phase, were passed during the crisis. The results show that during the release phase there were various problems that arose, starting from a lack of capacity, prices that were too high, as well as member safety and comfort. Meanwhile, in the reorganizing phase, the resilience of the co-working space comes from member loyalty which is built from various means, such as listening to members complaints and providing the best service that create word of mouth from the member itself. Keywords: Resilience Strategy, Co-working Space, Digital Nomadism, Digital Nomad